2014
DOI: 10.1007/s12105-014-0543-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytic Lipoadenoma of the Salivary Gland: A Clinicopathologic Analysis of 7 Cases and Review of the Literature

Abstract: Oncocytic lipoadenoma is an exceedingly uncommon neoplasm of the salivary gland composed of oncocytic epithelium and adipose tissue. Retrospective. Seven cases of oncocytic lipoadenoma were analyzed in order to further characterize the clinical and pathologic features of this rare tumor. The patients included six males and one female who ranged from 40 to 83 years of age (mean 62 years) at presentation. All tumors arose in the parotid gland. Grossly, the tumors were solitary, well circumscribed and had light b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…1 Oncocytic lipoadenoma is a very rare benign tumor of the salivary gland that was first described by Hirokawa et al 4 After that, few other cases of oncocytic lipoadenoma have been reported; most of those reported cases were arising in the parotid gland with only four cases reported to occur in the submandibular gland. [3][4][5][6][7][8][9][10] Our patient presented with a swelling at the right angle of mandible which revealed by ultrasound that it was arising from the subman- In summary, we are reporting a rare case of oncocytic lipoadenoma arising in the submandibular gland. Our aim is to upsurge awareness among cytopathologists during preoperative evaluation of oncocytic salivary gland lesions.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…1 Oncocytic lipoadenoma is a very rare benign tumor of the salivary gland that was first described by Hirokawa et al 4 After that, few other cases of oncocytic lipoadenoma have been reported; most of those reported cases were arising in the parotid gland with only four cases reported to occur in the submandibular gland. [3][4][5][6][7][8][9][10] Our patient presented with a swelling at the right angle of mandible which revealed by ultrasound that it was arising from the subman- In summary, we are reporting a rare case of oncocytic lipoadenoma arising in the submandibular gland. Our aim is to upsurge awareness among cytopathologists during preoperative evaluation of oncocytic salivary gland lesions.…”
Section: Discussionmentioning
confidence: 78%
“…Oncocytic lipoadenoma is a very rare benign tumor of the salivary gland that was first described by Hirokawa et al After that, few other cases of oncocytic lipoadenoma have been reported; most of those reported cases were arising in the parotid gland with only four cases reported to occur in the submandibular gland …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review of the English‐language literature identified 29 previous oncocytic lipoadenomas of the salivary glands . There were 17 males (59%) and 12 females (41%), with an average age of 57 years (range 7–89 years).…”
mentioning
confidence: 99%